PENGEMBANGAN MEDIA PAPAN OPERASI HITUNG PADA MATA PELAJARAN MATEMATIKA KELAS IV DI SEKOLAH DASAR. - Purnama, Titis Mey; Kudsiah, Musabihatul; Mahmudah, Rifaatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by students' difficulties in understanding arithmetic operations. This is influenced by the dominant lecture method used by teachers and the lack of innovative learning media, resulting in students having difficulty understanding the material and tending to be less motivated to learn. The purpose of this study is to develop a valid and practical Arithmetic Operations Board learning medium that can help students understand arithmetic operations more easily, enjoyably, and interestingly.This research is a Research and Development (R&D) study using the 4D development model consisting of the Define, Design, Develop, and Disseminate stages. However, this research is limited to the Develop stage for certain considerations. The instruments used in this study were validation sheets for material experts and media experts, as well as teacher and student response questionnaires to determine the media's practicality. The subjects of this study were fourth-grade students at SDN 1 Dane Rase, with 18 respondents. Based on the media validation results, the results obtained a score of 97.22% and the results obtained a score of 97.22% for the material validation, with the criteria being